Evaluating Rabies Test Accuracy: A Systematic Review and Meta-Analysis of Human and Canine Diagnostic Methods - Mayron Antonio Candia-Puma; Leydi Pola-Romero; Haruna Luz Barazorda-Ccahuana; Luis Daniel Goyzueta-Mamani; Alexsandro Sobreira Galdino; Ricardo Andrez Machado-de-Ávila; Rodolfo Cordeiro Giunchetti; Eduardo Antonio Ferraz Coelho; Miguel Angel Chávez-Fumagalli (Diagnostics)
Background/Objectives: Rabies is almost invariably fatal once clinical symptoms manifest. Timely and accurate diagnosis is essential for effective treatment and prevention. Dogs are the principal reservoirs of the virus, particularly in developing nations, highlighting the importance of precise diagnostic and control measures to prevent human cases. This systematic review and meta-analysis assessed the accuracy of laboratory tests for diagnosing rabies in humans and dogs. Methods: The PubMed database was searched for published studies on rabies diagnosis between 1990 and 2024. Following PRISMA statement recommendations, we included 60 studies that met the selection criteria. Results: The results demonstrated the effectiveness of immunological tests like the Enzyme-Linked Immunosorbent Assay (ELISA) and molecular tests such as Reverse Transcription Polymerase Chain Reaction (RT-PCR) for both humans and dogs. In this study, the Direct Fluorescent Antibody Test (DFAT) exhibited lower diagnostic performance, with an area under the curve for false positive rates (AUCFPR = 0.887). In contrast, ELISA (AUCFPR = 0.909) and RT-PCR (AUCFPR = 0.905) provided more consistent results. Notably, the Rapid Immunochromatographic Test (RIT) showed the best performance (AUCFPR = 0.949), highlighting its superior diagnostic capabilities compared to DFAT. Conclusions: These findings underscore the need to modernize rabies diagnostic protocols by incorporating advanced methodologies to improve diagnostic accuracy, reduce transmission, and decrease mortality rates.